Theater as an artistic and social language to dialogue against gender-based violence within the framework of the XXXII Festival of Women on Stage for Peace (The Voz a Vos Bulletin, 2023)
Understanding theater as a critical language and enabler of peace, I attend the Festival of Women on Stage for Peace, held from August 4 to 13, created and directed by Patricia Ariza who is aware of the reality of the country and accompanied by a group of women. consolidates a meeting that has three factors that make it unique and important for society: women, theater, and peacebuilding.This festival has the participation of women and artists who seek to generate dialogues between the arts and the social responsibility that we all have as political subjects. This year was the thirty-second version, on this occasion eighty-five plays, dances, and performances were presented in ninety-five functions, involving thirty-two stages. Forty groups were from Bogotá, but it also had the participation of twenty-three national groups and nineteen international groups. In addition to the above, seven workshops, book launches, and a poetry recital were held at this women's festival. The closing event was the XII Polyphonic Meeting of Women and Peace in which leaders, artists, and women of all ages had the opportunity to meet, listen to, and recognize each other collectively, taking into account different knowledge and voices, to build proposals for advance peace with women from different countries and territories of Colombia. This meeting aims to reflect on the commitments, priorities, and challenges we have to achieve social, political, economic, and cultural transformations.I had the opportunity to attend ten plays and interview seven women actors, directors, playwrights, and artists, who contribute through art to generate social change. This research has been systematized in my degree work: Theater as an artistic and social language to dialogue against gender-based violence within the framework of the XXXII Festival of Women on Stage for Peace.